Tax expenditure management - Burton, Mark (Cambridge University Press, 2013)
Includes bibliographical references and index.; A tax expenditure is a 'tax break' allowed to a taxpayer or group of taxpayers, for example, by way of concession, deduction, deferral or exemption. The tax expenditure concept, as it was first identified, was designed to demonstrate the similarity between direct government spending on the one hand and spending through the tax system on the other. The identification of benefits provided through the tax system as tax expenditures allows analysts to consider the fiscal significance of those parts of the tax system which do not contribute to the primary purpose of raising revenue. Although a seemingly simple concept, it has generated a range of complex definitional and practical issues, and this book identifies and critically assesses the controversial aspects of tax expenditure and tax expenditure management.